Paradigms of intraoperative neuromonitoring in paediatric thyroid surgery - Yuchuan Li; Chunhai Zhang; Yi Zhang; Gianlorenzo Dionigi; Gianlorenzo Dionigi; Yishen Zhao; Hui Sun; Hui Sun; Yingying Wang (Frontiers in Endocrinology)
The larynx of children and adolescents is still in the developmental phase and the anatomical structure is still very small and sensitive. The higher malignancy and faster progression of some paediatric thyroid cancers make surgery more difficult. Intraoperative neuromonitoring (IONM) is frequently used in thyroid surgery as an effective means of securing the recurrent laryngeal nerve (RLN). Little information is available on the clinical efficacy of IONM in paediatric surgery. In addition, classic IONM techniques such as reinforced tracheal tube models with integrated surface electrodes are not standardised for children and adolescents. The use of innovative devices such as laryngeal masks with surface electrodes and thyroid cartilage receiving electrodes could replace monitoring tubes as a new form of IONM. Tracheal intubation in children needs to be performed by a highly experienced anaesthetist. The continued maturation of AI technology could be attempted in the future in conjunction with IONM to further reduce RLN injuries in children and adolescents. This article describes the anatomical features of the paediatric larynx, which differ from those of adults, and the advantages and shortcomings of IONM techniques for thyroid surgery in this population. The use of IONM in paediatric surgery is a complex technique and should be performed by experienced thyroid surgeons with in-depth IONM training. The use of IONM should be standardised within the clinical parameters of children.